(untitled) (Laisvalaikio tyrimai, 2018)
Objective – Rate the leisure time and work quality indications. Methods – Questionnaire survey. Relevance of the research. There are not many investigations related to psychosocial work characteristics and employees’ age. The majority of investigations are more focused on work characteristics and other variables, especially health, connections and more concentrating on their age; however they do not tend to focus on work characteristics and connections with demographic measures. Research aim was to reveal the leisure time and work quality indications and the influence of these indications in the relationship between leisure time and work time. There were 396 respondents in this investigation. Research results and conclusions. Analysis of scientific literature revealed that leisure time was defined and understood as free time from necessary activities. This time is dedicated to accommodate ones needs, also to widen the circle knowledge, develop skills and to improve both physical and spiritual status. Work is an absolutely obligatory part of the person’s life which takes a lot of person’s time. Essential indicators disclose the leisure time and work quality indications which consist of work characteristics, the environment and person’s identity module. The research confirmed that qualitative indications that determine leisure time and work quality are the following: improving personal abilities at work, physical, psychological and emotional efforts at work, given support at work if mistakes are made, work expectation satisfaction in the work activities, stress and regulation levels at work, work quality after leisure time, occurrence of free time after work, active and passive leisure time and its chosen form and time, enjoyable activities, thinking about work while having leisure time, leisure time with friends and family. The most important and highest rated are these indications: spending leisure time with friends or family, improving personal abilities at work, the support at work, productive leisure time, etc., the less important ones are stress, regulation and control while working, physical, psychological and emotional effort at work, etc. It is important to emphasize that today it is relevant to discover the balance between work and leisure time as this appropriate balance can be valued as a preventive tool to avoid harmful habits and the reason why essential health care expenses are minimised. Keywords: leisure, work, quality indication.